Isolation and identification of microalgae as omega-3 sources from mangrove area in Aceh Province - Sri Haryani Anwar; M. Ikhsan Sulaiman; Syarifah Rohaya; Novi Safriani (Syiah Kuala University, 2013)
Omega-3 fatty acids such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are essential fatty acids with numerous health benefits. The main sources of these fatty acids are fish and fish oils. However, fish supply is limited and the availability is uncertain. There are two main problems with regard to fish supply: overfishing and mercury contamination. In addition, food enrichment with fish oil is apparently challenging due to sensitivity of fish oil to oxidation, and fishy smell which make them less attractive to consumers. Based on above problems, alternative sources of EPA and DHA must be found. Analternative for omega-3 fatty acids are microalgae. This research aims to isolate, identify, and find microalgae biodiversity that are able to produce omega-3 fatty acids in their cells. Microalgae were isolated from fallen, senescent leaves of mangrove tree (Kandelia candel) in two locations in Aceh. The colonies were identified morphologically using light and stereo microscopes with 1000x magnifications. The results were compared with those in literatures. This research has isolated and identified some genus of microalgae thatwere predicted belong to order Labyrinthulida and family Thraustochytriidae. Morphological observations have also confirm identification of one fungi, genus Mortierella. All identified microalgae and fungi are omega-3 fatty acids producers, mainly EPA and DHA